2011
DOI: 10.1111/j.1600-0579.2011.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, educational experiences and attitudes towards child abuse amongst Jordanian dentists

Abstract: Background:  Signs of physical abuse often present in the oro‐facial region and dentists are in a strategic position to recognise and report suspected cases. The aim of this study was to assess the knowledge, educational experiences and attitudes of Jordanian dentists towards child abuse and to assess their educational needs. Methods:  A cross‐sectional survey of a random sample of Jordanian dentists (n = 400) was conducted using an anonymous, self‐administered structured questionnaire. Results:  The response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
65
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 19 publications
(48 reference statements)
13
65
0
9
Order By: Relevance
“…Synonymous to studies by Sonbol et al 17 (57%) and Al-Dabaan et al 4 (74.6%), our study also revealed that children of low socioeconomic status (77%) are more commonly predisposed to physical maltreatment. Parent unemployment, poverty and child maltreatment have been identified as risk factors for the same.…”
Section: Population and Gender Group At Risksupporting
confidence: 85%
“…Synonymous to studies by Sonbol et al 17 (57%) and Al-Dabaan et al 4 (74.6%), our study also revealed that children of low socioeconomic status (77%) are more commonly predisposed to physical maltreatment. Parent unemployment, poverty and child maltreatment have been identified as risk factors for the same.…”
Section: Population and Gender Group At Risksupporting
confidence: 85%
“…Dalledone et al stated that 35.67% of the dentists reported suspected cases to authorities in Brazil. There are many studies from all over the world which reported similar findings . In the present study, most of the students stated the reasons for not reporting child abuse were fear of anger from parents and family, lack of knowledge regarding the referral procedure and uncertainty about the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] A marked increase in reported cases of suspected child abuse by the dental profession can occur by educating dentists and also when child protection teams comprise of a dentist. Dentists who have been educated to recognize signs of abuse and neglect are 5 times more likely to make a report than dentists who are not.…”
Section: Dentists Responsibly and Reportingmentioning
confidence: 99%